THE IMPORTANCE OF ATTRACTING FOREIGN INVESTMENTS IN THE DEVELOPMENT OF THE SMALL BUSINESS SECTOR (World Economics and Finance Bulletin, 2024)
In the social and economic development of the country, the Tax Code of the Republic of Uzbekistan has introduced permanent and fixed benefits for small business entities, as well as by special decisions of the Government. Enterprises with participation of foreign investments have the right to use these privileges in accordance with the laws, like local enterprises
Keywords: small business; social and economic development; foreign investment